Innovative Building Materials Using Agricultural Waste. (2015) - (Andres), Dana Maria Cantor; Manea, Daniela Lucia
Abstract: The objective of this paper is to present the researches about an innovative material, a composite material made up of two components: matrix - plain concrete, prepared according to NE 012 / 1-2007 and reinforcing material represented by wheat straw. The most common agricultural waste is wheat straw, which is often burned in the field, contributing to carbon dioxide emissions, annually recurring phenomenon that has become a concern to the appropriate authorities. The research objective seeks to eliminate traditional operations made with wheat straw (burning) and obtain materials with innovative features.